Perbandingan dua metode analisis konsentrasi mikroplastik pada kerang hijau, Perna viridis dan penerapannya dalam kajian ekotoksikologi (Comparison of two methods of analyzing microplastic concentrations of green mussels, Perna viridis, and their application in ecotoxicological studies) - Liestiaty Fachruddin; Khusnul Yaqin; Reski Iin (Program Studi Manajemen Sumber Daya Perairan, 2020)
Microplastic has become a pollution problem that has received serious attention from people to scientists. There are several microplastic analysis methods in mussel tissue. This study examines two analytical methods, namely non-filtration and filtration methods. 99 samples of green mussels, Perna viridis, were collected by hand from the waters of Lae-Lae Island in Makassar. For the purposes of the study, green mussels are grouped in various ranges of shell lengths that are 4-5.9 cm (small); 6-7.9 cm (medium) and 8-10 cm (large). T-student test was used to determine the difference in the average concentration of microplastic in the mussel with two different techniques used. The ANOVA parametric test was used to calculate the difference in the average microplastic concentration between different lengths of shell lengths. The results showed that the concentration of microplastics found in the tissue of the green mussel is in the form of fiber. From the results of statistical analysis it was found that microplastic analysis techniques with filtration were able to obtain more microplastic concentrations compared to non-filtration techniques. The results of this study also showed that the longer the size of the shell the less the concentration of microplastic shells. Therefore it was concluded that the larger the size of the green mussel the less the concentration of microplastic in the tissue.